Choledocoduodenostomy in patients aged over 75 - Beguiristain, Alberto; Carriquiry, Guillermo; Domínguez, Juan; Armand Ugon, Alfredo; Estefan, Alberto (Cirugía del Uruguay, 1984)
Retrospectiva study of 36 patients aged over 75, with cholelithiasis and treated by choledochoduodenostomy. The high incidence of extrabiliary pathology was the cause of the morbimortality observad. Results of treatment of biliary pathology were exce lent. Emphasis is laid on the treat"ment of prior associated diseases.